Impact of Different Types of Physical Activity in Green Urban Space on Adult Health and Behaviors: A Systematic Review - Alessia Grigoletto; Mario Mauro; Pasqualino Maietta Latessa; Vincenzo Iannuzzi; Davide Gori; Francesco Campa; Gianpiero Greco; Stefania Toselli (MDPI AG, 2021)
This systematic review aimed to investigate the type of physical activity carried out in green urban spaces by the adult population and to value its impact on the population's health. Additionally, another purpose was to examine if the presence of outdoor gyms in green urban spaces can promote participation in physical activity among adults. Searches of electronic databases, with no time restrictions and up to June 2020, resulted in 10 studies meeting the inclusion criteria. A quantitative assessment is reported as effect size. Many people practiced walking activity as a workout, which showed improvements in health. Walking is the most popular type of training due to its easy accessibility and it not requiring equipment or special skills. Outdoor fitness equipment has been installed in an increasing number of parks and has become very popular worldwide. Further, outdoor fitness equipment provides free access to fitness training and seems to promote physical activity in healthy adults. However, other studies about outdoor fitness equipment efficiency are needed. People living near to equipped areas are more likely to perform outdoor fitness than those who live further away. The most common training programs performed in green urban spaces included exercises with free and easy access, able to promote physical health and perception.